Hardware is Hard: An exploration of why developers fail to deliver crowdfunded products on time - Berglund, My (My University, 2020)
Few developers successfully manage to crowdfund hardware products. And those who accomplish such a feat face another challenge – fulfilment. Despite their initial success many developers failed to deliver products on time. This study explores these failures. Successfully funded but delayed hardware projects from Kickstarter were identified using a web scraped dataset. A qualitative content analysis was carried out on the projects to explore what affects timeliness. Three themes were established based on the findings; quality of partnerships, developers’ knowledge, and the extent of uncertainty. The findings were furthermore compared to two previous research streams; traditionally funded product developments and crowdfunded product development. This comparison showed that the study’s findings aligned well with previous research. A notable point of difference was DFM, design for manufacturability practices. Whereas this DFM is understood and practised within traditionally funded product development, in the crowdfunding context it was given surprisingly little regard. Consequently, the results indicate that developers choosing to crowdfund could benefit from applying traditional strategies to mitigate and eliminate delay, especially in the area of manufacturability.
Keywords: Crowdfunding, New Product Development, Kickstarter, Delays, Timeliness